NEW RECORD OF DOLICHOPODA FROM NORTHERN IRAN (Orthoptera, Rhaphidophoridae) - Di Russo, Claudio; Rampini, Mauro (Fragmenta entomologica, 2013)
The record of a new sample of Dolichopoda from Northern Iran is reported. The morphological study of this material allowed the authors to attribute the studied specimens to D. Hyrcana Bey-Bienko, 1969, whose geographic distribution now extends eastwards to the Alborz Mountains in North Iran.